The Role of Industrial Environment and Innovation Phenomenon Analysis in the Development of Batik Small and Medium-sized Enterprises in Malang and Batu - Andi Normaladewi (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2016)
Abstract: The study analyzes the role of Batik SME’s industrial environment based on Porter’s Five Competition Forces. This study also analyzes the phenomenon of innovation in the expansion of Batik SME based on the type and nature.Method applied in this study uses phenomenological approach to describe and analyze phenomenon, events, social activities, behaviors, beliefs, and perceptions of batik entrepreneurs. The findings of this study are, first, product information makes customers more selective in choosing their batik needs offered; second, batik entrepreneurs collaborate with suppliers in Yogyakarta, Solo, and Pekalongan by purchasing tools and batik materials in large quantities. Batik entrepreneurs of Celaket act as suppliers of batik tools and materials as well especially in the area of Malang and Sukun; third, Batik SME in Malang and Batu are confronted by the presence of other businesses that produce dyed batik and printed batik, which are new kinds in the world of batik. Printed batik (batik printing) and dyed batik (batik celup) are produced in large quantities with fast processing time and very low price, so the traditional batik entrepreneurs deal with the competition by maintaining and improving the quality of batik and applying an appropriate pricing strategy; fourth, the dynamic environment of industry triggers some entrepreneurs to innovate in order to maintain existence in the world of batik.Finally, there is a value shift in the art of batik culture both motifs and philosophy due to market demand and economic needs. Keywords: Industrial Environment, Porter’s Five Competition Forces, Innovation Phenomenon, Batik SME Abstrak: Penelitian ini menganalisis peran lingkungan industry Usaha Kecil Menengah (UKM) Batik berdasarkan Lima Tekanan Kompetisi Porter. Penelitian ini juga menganalisis fenomena inovasi dalam ekspansi UKM Batik berdasarkan tipe dan sifat alami batik. Metode yang diaplikan dalam penelitian ini adalah pendekatan Fenomenologi untuk mendeskripsikan dan menganalisis fenomena, kejadian-kejadian, aktivitas sosial, perilaku, kepercayaan, dan persepsi pengusaha batik. Hasil penelitian adalah, pertama, informasi produk membuat konsumen lebih selektif memilih batik yang ditawarkan; kedua, para pengusaha batik berkolaborasi dengan supplier di Yogyakarta, Solo, dan Pekalongan dengan membeli peralatan dan bahan baku batikdalam jumlah besar. Pengusaha batik Celaket berperan sebagai supplier peralatan dan bahan baku batik khususnya di kawasan Malang dan Sukun; ketiga, UKM batik di Malang dan Batu menghadapi perlawanan dari kehadiran bisnis baru yang memproduksi batik celup dan batik printing yang merupakan varian baru dalam dunia perbatikan. Batik printing dan batik celup diproduksi dalam jumlah yang besar dengan waktu proses cepat dan harga yang sangat rendah, sehinggapengusaha batik tradisional mengatasi masalah ini dengan menjaga dan atau meningkatkan kualitas batik dan mengaplikasikan strategi harga yang tepat; keempat, dinamika lingkungan industry memicu beberapa pengusaha batik berinovasi untuk menjaga eksistensi di dunia perbatikan; dan terakhir, ada pergeseran nilai dalam budaya seni batik meliputi motif dan filosofi karena permintaan pasar dan kebutuhan ekonomi. Kata Kunci: Lingkungan Industri, Lima Tekanan Kompetisi Porter, Fenomena Inovasi, UKM Batik